Analisis Determinan Perilaku Keuangan Guru Honorer Sekolah Dasar Di Kecamatan Karang Tengah Kota Tangerang - Wahyudi Wahyudi; Yoko Tristiarto (Universitas Persada Indonesia YAI, 2022)
This study is a quantitative study that aims to determine the effect of financial literacy,financial technology, and income on financial behavior. The population in this study were honoraryelementary school teachers in the district of Karang Tengah, Tangerang city. Samples were takenas many as 80 respondents, with non-probability sampling method, purposive sampling. Data wascollected through the distribution of questionnaires. The analytical technique used is the PLS(Partial Least Square) analysis method with SmartPLS 3.0 software. The results of this studyindicate that (1) financial literacy has a significant positive effect on financial behavior. (2) financialtechnology has no influence and is not significant on financial behavior. (3) income has a significantpositive effect on financial behavior.